Antimicrobial potential of four mica drugs and their chemical and mineralogical properties - Apsara Wijenayake; Charmalie Abayasekara; Amarasooriya Pitawala; B. M. Ratnayake Bandara (BMC, 2022)
Abstract Background Mica drugs, a group of herbo-metallic traditional preparations comprising biotite mica as the major mineral ingredient, are prescribed for skin disorders and respiratory ailments and other chronic conditions in South Asian countries, particularly India and Sri Lanka. Mica-based drugs (Abhrak drugs) are subjected to unique and varied preparation procedures and the bioactivity of the drugs can be affected by drug-processing conditions, the ingredients used and the mica composition. The current study aimed to evaluate and compare, on the basis of their physical and chemical characteristics, the antimicrobial potential of two commercial mica drugs AbBb (Abhrak bhashma) and AbCh (Abhrak Chenhuram) and two mica drugs ABL1 (Abhrak Bhasma Laboratory Prepared 1) and ABL2 (Abhrak Bhasma Laboratory Prepared 2) prepared in the laboratory under different conditions. Methods Antimicrobial activity of all four drugs was assessed at 10 mg/ml concentration against Pseudomonas aeruginosa, Escherischia coli, Staphylococcus aureus, methicillin-resistant S. aureus (MRSA) and Candida albicans using well diffusion assay, agar dilution assay and Miles and Misra method. Major and trace metal constituents of the drug samples were measured using atomic absorption spectrometry. Mineralogical properties, bacteria-mineral interactions, morphological changes in microbes and the surface characteristics of the drugs were determined using X-ray diffraction (XRD) analysis and scanning electron microscopy (SEM). Results The drugs ABL1, ABL2 and AbBh exhibited antimicrobial activity against only Gram-positive organisms (S. aureus and MRSA) when tested with Miles and Misra method (broth method). Mineralogical studies (XRD) revealed that biotite mica was altered into secondary clay minerals and iron oxides in the commercial drug AbCh while the other three drugs had altered mica and iron oxide phases. The essential elements (Na, K, Ca and Mg) required for microbial functions were present in varying extents in all four drugs while they were present in exceedingly high amounts in AbCh having comparatively high cation-exchange capacity, consistent with the observation that AbCh was inactive against all the microbes tested. The three drugs (ABL1, ABL2 and AbBh) showing antimicrobial activity contained comparatively high amounts of Fe, Zn and Cu that are known to display antimicrobial properties at high concentrations. SEM studies revealed that the drug particles adhered and entrapped the bacterial species, presumably modifying the physiochemical characteristics of the bacteria and eventually causing lethality. Conclusion Three of the four mica drugs inhibited the tested Gram-negative bacteria and the antibacterial activity of the mica drugs depends on their constituents and the methods of preparation.